Peran Model Pembelajaran Berbasis Proyek Dalam Mendorong Perkembangan Kognitif Anak Usia Dini - Sri Jumiaty Permatasari; Itsnain Alfajri Husain; Chairan Zibar L. Parisu (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2025)
The project-based learning model (PjBL) has become one of the relevant approaches in early childhood education because it provides space for exploration, direct experience, and active participation of children in the learning process. This study aims to theoretically examine how the application of PjBL can encourage the cognitive development of early childhood. Through the literature study method of various scientific sources published in the last five years (2020–2025), it was found that the application of PjBL consistently correlates with increased cognitive functions such as critical thinking skills, observation, classification, reflection, and early literacy. Project activities allow children to be involved in direct observation of objects, make predictions, organize categories, and convey ideas verbally and visually. In addition, PjBL also encourages children's independence in decision-making and the development of creativity in completing simple tasks independently. Simple projects such as environmental exploration, making creative products, and simulating social roles have been shown to stimulate children's logical and systematic thinking skills. The role of the teacher as a facilitator is crucial in designing projects that are appropriate to the child's developmental stage and interests. The conclusion of this study shows that PjBL is not only an effective method in strengthening cognitive aspects, but also provides an important foundation for children's readiness in facing learning at the elementary education level. This approach is also in line with the spirit of 21st century learning which emphasizes collaboration, creativity, and problem solving.